Co-infection of TYLCV and ToCV increases cathepsin B and promotes ToCV transmission by Bemisia tabaci MED - Lu, Ding-Yi-Hui; Liao, Jin-Yu; Fajar, Anugerah; Chen, Jian-Bin; Wei, Yan; Zhang, Zhan-Hong; Zhang, Zhuo; Zheng, Li-Min; Tan, Xin-Qiu; Zhou, Xu-Guo; Shi, Xiao-Bin; Liu, Yong; et al. (Frontiers in Microbiology, 2023)
Tomato disease is an important disease affecting agricultural production, and the combined infection of tomato chlorosis virus (ToCV) and tomato yellow leaf curl virus (TYLCV) has gradually expanded in recent years, but no effective control method has been developed to date. Both viruses are transmitted by Bemisia tabaci Mediteranean (MED). Previously we found that after B. tabaci MED fed on ToCV and TYLCV-infected plants, the transmission efficiency of ToCV was significantly higher than that on plants infected only with ToCV. Therefore, we hypothesize that co-infection could enhance the transmission rates of the virus. In this study, transcriptome sequencing was performed to compare the changes of related transcription factors in B. tabaci MED co-infected with ToCV and TYLCV, and infected only with ToCV. Hence, transmission experiments were carried out using B. tabaci MED to clarify the role of cathepsin in virus transmission. The gene expression level and enzyme activity of cathepsin B (Cath B) in B. tabaci MED co-infected with ToCV and TYLCV increased compared with those under ToCV infection alone. After the decrease in cathepsin activity in B. tabaci MED or cathepsin B was silenced, its ability to acquire and transmit ToCV was significantly reduced. We verified the hypothesis that the relative expression of cathepsin B were reduced, which helped reduce ToCV transmission by B. tabaci MED. Therefore, it was speculated that cathepsin has profound research significance in the control of B. tabaci MED and the spread of viral diseases.